1981
DOI: 10.1079/bjn19810007
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the rumen proteolysis of fraction I (18S) leaf protein from lucerne (Medicago sativa L)

Abstract: 1. The rate of proteolysis of fraction I (18s) leaf protein in the rumen of sheep and cattle was affected by diet and the rate on fresh lucerne ( Medicago sativa L) was three to nine times the rate on a hay + concentrate diet.2. Simultaneous rumen fermentations in vivo and in an artificial rumen showed that the rates of proteolysis of fraction I in vitro was approximately 80% of the rates in sheep.3. Using I4C uniformly-label ed fraction I protein at low concentrations, proteolysis exhibited 1st-order kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
88
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 19 publications
4
88
0
Order By: Relevance
“…Bacteria have been reported to be primarily responsible for the degradation of plant protein, and protozoa were thought to only have a minor role in this metabolic activity [48]. In this regard, Wallace and Cotta [66] reported that the role of protozoa in ruminal protein degradation is mostly related to the degradation of feed particles and bacterial proteins, but their overall effect on protein degradation is still controversial.…”
Section: Estimation Of Microbial Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria have been reported to be primarily responsible for the degradation of plant protein, and protozoa were thought to only have a minor role in this metabolic activity [48]. In this regard, Wallace and Cotta [66] reported that the role of protozoa in ruminal protein degradation is mostly related to the degradation of feed particles and bacterial proteins, but their overall effect on protein degradation is still controversial.…”
Section: Estimation Of Microbial Growthmentioning
confidence: 99%
“…In this regard, Wallace and Cotta [66] reported that the role of protozoa in ruminal protein degradation is mostly related to the degradation of feed particles and bacterial proteins, but their overall effect on protein degradation is still controversial. Most of the protease is cell bound [48,52]; only a small portion is extracellular [1]. In this regard, protease activities in SRFWP and EABC are higher than in CFRF.…”
Section: Estimation Of Microbial Growthmentioning
confidence: 99%
“…(1985). The (Nugeant and Mangan, 1981 Therefore, the degradation of soluble proteins may be more intense in the defaunated than in the faunated rumen. This hypothesis is supported by the fact that proteolytic activity was higher in defaunated animals when measured using azocasein which is totally soluble.…”
mentioning
confidence: 99%
“…The proteolytic bacteria are mainly involved in the degradation of plant protein (Nugent & Mangan, 1981), whereas the rumen ciliate protozoa are thought to degrade bacterial and insoluble particulate proteins (Hino & Russell, 1987;. The predation of the bacteria by ciliates increases the rate of bacterial protein turnover (Wallace & McPherson, 1987) and decreases the efficiency of bacterial growth in the rumen (Veira, 1986), and defaunation (i.e.…”
Section: Introductionmentioning
confidence: 99%